WOMEN ENTREPRENEURSHIP IN INDIA : PROBLEMS AND PROSPECTS - Nomu Pawe, Devajit Saikia, Barnali Doley (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Now a days, women entrepreneurs are playing a vital role in India and it is become an important part of the global business environment. The concept of women entrepreneurs refers to a organization/business which is started by a woman or a group of women; for the purpose of economic development and social progress. But Indian women entrepreneurial ability has not been properly tapped due to the lower status of women in the society. Basically Indian sociological set up has been a male dominated one. Despite all the social obstacles, Indian women stand tall from the rest of the crowd and are applauded for their achievements in their respective field. The progress of in Indian women due to growth in education, urbanization, industrialization and awareness of democratic values. This paper include the concept of women entrepreneur -Factors responsible for encouraging women to become entrepreneurs -Reasons for slow progress of women entrepreneurs in India -Steps for the growth of women entrepreneurs -Schemes undertake by Government for the development of women in India.